Gamification for Student Achievement in Classroom: In Search of Requirement for Student Achievement Application - Rayinda Pramuditya Soesanto (International Journal of Innovation in Enterprise System, 2021)
There are numerous methods available in the education arena for increasing student participation inclass. The experience that students have during class is critical not just for the students, but also forthe instructor. Student achievement in the classroom can be increased to the point that the studentenjoys performing class tasks. Problems arise when the students are burned out because they areexhausted by learning, especially online learning during the pandemic situation. It is necessary todevelop an application that may be utilized as a tool to assist teachers and students in managing studentachievement through the use of gamification. The objective of this study is to ascertain whichrequirements and functions should be incorporated into the design of the student achievementapplication. User centered requirement engineering approach is used in this research to elicit therequirement from the users. Lecturers and students were employed as respondents in this study toascertain the development phase's priorities and essential functions. The application's functions andcharacteristics are separated into two broad categories: technical and usability / content. The Delphitechnique is used to identify the function/characteristics. Further research could be conducted todevelop systems / applications based on the functional requirements identified during the study inorder to develop a student achievement application.